EXPLOITATION AND HYDROGEOLOGICAL PARAMETERS OF HYDROGEOTHERMAL SYSTEM SPA KEZHOVICA - STIP - Mirchovski, Vojo; Dimov, Gorgi; Gerasimov, Darko (Natural Resources and Technology, 2017)
This paper presents the exploitation and hydrogeological parameters of hydrogeothermal system of the spa Kežovica, which are calculated based on data obtained by the pump testing of the four exploitation wells that are located within this system, labeled as B-1, B-2 , B-3 and S-3. The individual exploitation capacity of the wells is for B-1 - 1,7 l/s; for B-2 -12,5 l/s, B-3 - 8,9 l/s and for S-3 - 3,3 l/s, and the total capacity of exploitation of all wells is 26,4 l/s. The coefficient of filtration of the aquifer medium is within ranges of 0,034 - 2,25 m/day, the transmissibility ratio is from the 3,3 to 38,29 m2/s, and the radius of the influence of the wells is in range from 49 to 155 m. The temperature of the thermomineral is from 52 to 62 ° C.